Super-resolution imaging of photogenerated charges on CdS/g-C₃N₄ heterojunctions and its correlation with photoactivity - Wu, Shuyang (2022)
Construction of heterostructures is an effective way to improve photo-induced charge separation and photocatalytic performance. Among various structures, type II and direct Z-scheme heterojunctions with distinct charge separation mechanisms are the two typical representatives attracting much research attention. Here we prepared type II and Z-scheme CdS/g-C3N4 nanocomposites by thermal treatment and self-assembly chemisorption methods, respectively. High-resolution microscopy techniques including (scanning) transmission electron microscopy (TEM/STEM) and super-resolution fluorescence microscopy (SRM) were used to investigate the charge distribution and flow mechanism. The charge tracking results reveal that the nanocomposite prepared by thermal treatment has a type II heterostructure with charges flowing in the opposite direction, while the self-assembly sample possesses a Z-scheme structure. It was found that the type II system exhibited the lowest charge migration resistance and the best charge separation ability and stability of photoactivity, leading to the highest H2 generation rate of 2410 μmol h-1 g-1. The SRM technique was applied for the first time to map the reactive sites of type II and Z-scheme structures at nanometer resolution. The photoactive species (i.e., e- and h+) were found to be preferentially distributed at the two end segments of CdS nanorods and the edge boundaries of g-C3N4. Therefore, our findings shed more light on the charge distribution and photocatalytic heterogeneity of composite materials at the nanoscale. Such results would provide guidance on optimizing nanocomposite properties and help to design better photocatalysts for efficient solar-to-chemical energy conversion.